Do Stool Form and Frequency Correlate With Whole-Gut and Colonic Transit? Results From a Multicenter Study in Constipated Individuals and Healthy Controls - Saad, Richard J; Rao, Satish SC; Koch, Kenneth L; Kuo, Braden; Parkman, Henry P; McCallum, Richard W; Sitrin, Michael D; Wilding, Gregory E; Semler, Jack R; Chey, William D (The American journal of gastroenterology, 2010)
Despite a lack of supportive data, stool form and stool frequency are often used as clinical surrogates for gut transit in constipated patients. The aim of this study was to assess the correlation between stool characteristics (form and frequency) and gut transit in constipated and healthy adults. A post hoc analysis was performed on 110 subjects (46 chronic constipation) from nine US sites recording stool form (Bristol Stool Scale) and frequency during simultaneous assessment of whole-gut and colonic transit by wireless motility capsule (WMC) and radio-opaque marker (ROM) tests. Stool form and frequency were correlated with transit times using Spearman's rank correlation. Accuracy of stool form in predicting delayed transit was assessed by receiver operating characteristic analysis. In the constipated adults (42 females, 4 males), moderate correlations were found between stool form and whole-gut transit measured by WMC (r=-0.61, P<0.0001) or ROM (-0.45, P=0.0016), as well as colonic transit measured by WMC (-0.62, P<0.0001). A Bristol stool form value <3 predicted delayed whole-gut transit with a sensitivity of 85% and specificity of 82% and delayed colonic transit with a sensitivity of 82% and specificity of 83%. No correlation between stool form and measured transit was found in healthy adults, regardless of gender. No correlation was found between stool frequency and measured transit in constipated or healthy adults. The correlation between stool frequency and measured transit remained poor in constipated adults with <3 bowel movements per week. Stool form predicts delayed vs. normal transit in adults. However, only a moderate correlation exists between stool form and measured whole-gut or colonic transit time in constipated adults. In contrast, stool frequency is a poor surrogate for transit, even in those with reduced stool frequency.